(untitled) (REMUNOM, 2024)
Mucoceles are common benign lesions in the oral cavity, frequently seen in children, usually caused by local trauma, with a higher incidence on the lower lip. Clinically, they appear as pedunculated nodules with external projections, with a smooth surface and a fibrous consistency to the touch, similar in color to the oral mucosa. From a histological point of view, they can be classified as mucus extravasation or mucous retention cysts. Treatment for mucoceles includes various options, such as complete removal of the lesion, marsupialization to allow drainage, cryosurgery using extremely low temperatures, the use of lasers and micromarsupialization. The choice of therapeutic method depends on the individual characteristics of the lesion and the patient’s needs. This case report describes the removal of a mucocele in a 7-year-old male patient with leukoderma. During the clinical examination, a circumscribed lesion was identified on the lower lip, with a smooth surface and a fibrous consistency to the touch, similar in color to the oral mucosa. After a detailed anamnesis and clinical examination, a probable diagnosis of mucocele was made. We opted for total surgical removal using an electric scalpel, a technique recognized for its efficacy and safety in minimizing complications and improving aesthetic and functional results. A sample of the lesion was subsequently sent for histopathological analysis, the result of which confirmed the presence of a mucocele. This case illustrates the importance of an appropriate and precise approach in the treatment of mucoceles, highlighting the effectiveness of the electric scalpel as a valuable tool in clinical practice for children’s oral surgical procedures. After one week, clinical control was carried out and complete healing of the site of the lesion was observed. In conclusion, the electric scalpel provided safe and simple removal of fibrous gingival tissue, resulting in reduced clinical procedure time, greater precision and better hemostasis. These factors contributed significantly to the child’s psychological conditioning.